(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Background: With increasing fungal disease many newer antifungal drugs are available with different spectrum of activity. Antifungal susceptibility test will help clinicians for selection of effective drug and thereby treatment of patient. Objective: The study was undertaken to perform a simple screening drug susceptibility test of T. rnbrum by Semi Solid Agar Antifungal Susceptibility (SAAS) Method: Perfonnance of susceptibility method was assessed by comparing the MICs of three commonly prescribed antifungal agents namely- tluconazole (FCZ), itraconazole (ITZ) and terbinafine (TER) to the CLSI (Clinical and Laboratory Standard Institute) recommended M-38, a broth microdilution method. Results: In SAAS method, among twenty nine T. rubrum, twenty five (86.2%) were susceptible (MIC range 0.5-64 µg/ml) to Fluconazole (FCZ) and four (13.7%) were resistant (MIC value >64 µg/ml). In broth microdilution method, among twenty nine T. rubrum, twenty six (89.6%) were susceptible (MIC range 0.3-64 µg/ml) to FCZ and three (10.3%) were resistant (MIC value >64 µg/ml). In case of both ITZ and TER, all were susceptible (MIC range 0.3-64 µg/ml) to both methods. The SAAS method demonstrated the susceptibility pattern of T. rubrum against FCZ, ITZ and TER usually within 72 to 96 hours after organism isolation and results were concordance with the results of CLSI broth microdilution method. Conclusion: Though it is a newer method with proper standardization of the test method, SAAS method is simple and easily applicable screening method for susceptibility testing of antifungal agents against dermatophytes in any microbiology laboratories.